[3+2]‐Cycloaddition for Fully Decorated Vinyl‐1, 2, 3‐Triazoles: Design, Synthesis and Applications. Issue 19 (27th August 2020) - Surendra Reddy, G.; Anebouselvy, K.; Ramachary, Dhevalapally B.
Abstract: The s mall heterocyclic ring of the 1, 2, 3‐triazole module is one of the most widely investigated compounds in numerous applications of biological, medicinal, pharmaceutical and materially important molecules. In this regard, a large number of synthetic methodologies and approaches have already been reported to construct such a heterocyclic core structure in a selective manner. However, the vinyl‐substituted 1, 2, 3‐triazole moiety is another privileged segment in heterocyclic chemistry. The selective introduction of simple vinyl and functionalized vinyl groups onto the three different positions of the 1, 2, 3‐triazole framework can significantly improve the properties of the molecule. Accordingly, high‐yielding efficient approaches for the selective construction of vinyl‐containing 1, 2, 3‐triazoles becomes a promising branch of chemistry among practitioners of industry and academia. In this minireview, we have discussed recent advances in the construction of highly selective three different vinyl‐containing 1, 2, 3‐triazoles. In addition, representative synthetic methodologies and approaches for the corresponding three different classes of vinyl‐1, 2, 3‐triazoles and their applications have been described as well in this review. Abstract : In the past two decades, we have witnessed tremendous growth in the selective synthesis of vinyl‐containing 1, 2, 3‐triazoles through [3+2]‐cycloaddition as a key reaction followed by functionalization through different reactions, and this Minireview summarizes the recent developments in this heterocyclic field, together with representative synthetic methodologies and applications.